Pengaruh PBL Berorientasi Fun Learning One Stay Another Stray Terhadap Keterampilan Komunikasi Siswa SMAN 1 Salimpaung: Penelitian - Galbinur, Elfi; Fadilah, Muhyiatul; D, Rahmawati; Rahmatika, Helsa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to determine the effect of Problem Based Learning oriented Fun Learning One Stay Another Stray on students' communication skills in biology learning. The biology material studied is the coordination system. The type of research used in this research is pre-experiment with one group pretest and posttest only design. The location of this research was conducted at SMAN 1 Salimpaung, Tanah Datar Regency, West Sumatra. The subjects of this study were students of class XI Phase F Moving Biology 3, as many as 17 students. The research instrument used was a written communication test in the form of pretest and posttest. The data analysis method used to determine the effectiveness of the treatment on students' communication skills using the N-Gain test. The results showed that the application of Problem Based Learning model oriented Fun Learning One Stay Another Stray had a positive effect with a moderate category on the communication skills of students in class XI Phase F Moving Biology 3 based on the average score of N-Gain. Written communication skills have increased with the criteria of N Gain medium score (g = 0.49).